SOCIODEMOGRAPHIC FACTORS AND ADOLESCENTS OVERWEIGHT: A SYSTEMATIC REVIEW (Fiep Bulletin - online, 2012)
Numerous epidemiological studies have been conducted around the world, seeking to quantify the role and interaction of factors in the etiology of obesity. The aim of this article is to conduct a systematic review of the literature on the association of sociodemographic factors, overweight and obesity in adolescence. The search for articles was conducted in Pubmed, with the main term “adolescent obesity”, which were added individually to the following descriptors: “socioeconomic status”, “demographic factors”, e “risk factors”; and in Scielo the terms: “overweight and adolescence” and “obesity and risk factors”. 1021 articles were identified of which 21 have contemplated all the inclusion criteria. With regard to socioeconomic status, in general, adolescents from lower social classes are more exposed to overweight in developed countries, the opposite occurring in developing countries. The inversion in the prevalence values among social strata coincides with the rise of the values of Human Development Index – HDI. The gender variable was not a significant effect to overweight, and age. It can be concluded that in adolescence, as well as in adult populations, certain population strata have a higher prevalence of overweight. As the course of transitions intensifies, this pattern tends to change mediated by the socioeconomic context.
Keywords: adolescents; overweigh; sociodemographic factors.